Overdose prevention in injecting opioid users: The role of substance abuse treatment and training programs - Ana Sarasa-Renedo; Albert Espelt; Cinta Folch; Carmen Vecino; Xavier Majó; Yolanda Castellano; Jordi Casabona; M. Teresa Brugal (Elsevier, 2014)
Objectives: Opioid overdose is still the first cause of preventable death among young men in Barcelona. Sound knowledge of opioid overdose prevention is important to avoid complications and deaths. This study aimed to identify the factors associated with limited knowledge of overdose prevention and to assess the possible effect of treatment and overdose prevention training programs on this variable. Methods: From October 2008 to March 2009, current injecting opioid users attending harm reduction centers in Catalonia (Spain) were interviewed. Crude and adjusted prevalence ratios of limited knowledge about overdose prevention were calculated by adjusting Poisson regression models with a robust variance. Results: In this sample, 28.7% of clients had limited knowledge of overdose prevention. Factors associated with limited knowledge were country of origin, never having received treatment for drug dependency, having a low educational level, and never having experienced an overdose. In contrast, treatment at the time of the interview was not associated with a lower prevalence of limited knowledge about overdose prevention. Conclusions: These findings suggest that preventive programs would benefit from accounting for linguistic and educational limitations and from participation in every treatment episode. Comprehensiveness and broad coverage of such programs could help to maximize their impact.